2022
DOI: 10.1177/15330338221075529
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Analysis of 50 Cases of Primary Pulmonary Lymphoma: A Retrospective Study and Literature Review

Abstract: Objective: This study aimed at to raise the awareness understanding of primary pulmonary lymphoma (PPL) by analyzing the clinical manifestation, imaging, pathology, diagnosis, treatment, and prognostic features of 50 cases of PPL. Methods: The study of 50 individuals with PPL diagnosed at the First affiliated hospital of Nanchang university between January 2009 and December 2019 was performed. Results: Overall, 27 males and 23 females were enrolled, with an average age of 57.6 ± 15.6 years. The primary symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 32 publications
(44 reference statements)
0
12
0
Order By: Relevance
“…In this case, PPL was diagnosed using an invasive VATS biopsy. The treatment options include surgery or radiotherapy for localized tumours and chemotherapy for multiple/diffuse involvement 2 . In this case, as multiple lung nodules were detected, we selected chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, PPL was diagnosed using an invasive VATS biopsy. The treatment options include surgery or radiotherapy for localized tumours and chemotherapy for multiple/diffuse involvement 2 . In this case, as multiple lung nodules were detected, we selected chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Diffuse large B‐cell lymphoma (DLBCL) is accounting for >10% of PPLs 1 . Radiologically, they can present as consolidation, infiltration, masses, and nodules with nonspecific findings 2 . Here, we report our experience with a case of PPL‐DLBCL detected as multiple pulmonary nodules and masses mimicking metastasis.…”
Section: Introductionmentioning
confidence: 96%
“…Multislice spiral CT of the chest is the preferred method for evaluating PPL, and thin-slice CT is more valuable for displaying detailed and characteristic images of lesions ( 26 ). Tumor cells of PPL can infiltrate and diffuse along the bronchial and vascular peripheral lymphatic sinus pathways, resulting in thickening of tissue structures around bronchial, vascular and lymphatic vessels or local formation of nodules or masses ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…(D) Mixed type: mixed with 2 or more pathological types, mostly pneumonia consolidation type and nodular mass type. In low-grade NHL, mass or nodular pneumonia and solitary lobular pneumonia are more common, whereas in high-grade NHL, multilobular lesions are more common ( 26 ). In our study, we observed that pneumonia consolidation type (42.1%) and nodular/mass type (36.8%) were the most common morphological pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Mucosa-associated lymphoid tissue lymphoma is the most frequent subtype, accounting for 60% to 80% of all the PPLs, followed by diffuse large B-cell lymphoma (10-25%). Others rare types of PPLs include LYG, mantle B-cell lymphoma and follicular lymphoma ( 16 ). About 36% of cases are asymptomatic at the time of diagnosis ( 17 ).…”
Section: Discussionmentioning
confidence: 99%